Three-Point Bending Behaviour of a Fabricated Concrete Connection with Steel Plate Hoop and Bolts - Dawei Yuan; Qingning Li; Jianpeng Sun; Jiaolei Zhang; Weishan Jiang (Advances in Civil Engineering)
As the development of building industrialization and housing industrialization is speeding up in China, the application of precast concrete structure has been the research focus. The connection of prefabricated components is one of the key technologies in prefabricated concrete structure. So, a new type of column–column connection with steel plate hoop and bolts is proposed in this paper to promote the application of precast concrete structure. In order to reveal the flexural behavior and force transfer mechanism about this new type connection, six precast concrete beams and one integral casting beam were tested by the three-point bending under loading and unloading cycle. The comparative analysis is made between the new type connection and traditional integral cast-in-place member from the aspects of test phenomenon, failure mode, and load-deflection relationship. The analysis results show that the new type connection has the same bending bearing capacity as the integral casting member. Based on the analysis of the load-strain relationship of longitudinal reinforcement, bolts, and steel plate hoop, the moment transmission mechanism and theoretical calculation formula of the new type connection are proposed, and the theoretical calculation results are consistent with the experimental results.